Monetary policy and inflation persistence in the Eurozone - Carlos J. Rodriguez-Fuentes; Antonio Olivera-Herrera; David Padron-Marrero (European Regional Science Association (ERSA), 2004)
The primary goal of the European Central Bank's (ECB) monetary policy is to achieve price stability. Whereas during the 1980s and 1990s there was a rapid and strong convergence in terms of price differential among the Euro countries, particularly in those countries with higher inflation rates in the past, single monetary policy has proved to be quite inefficient in continuing this trend and has not achieved further reductions in inflation rate differentials within the euro zone. Since the ECB sets the official interest rate according to the average inflation of the euro area, the persistence of such price differentials within the area would mean that the “one size interest rate policy” would not fit all. This paper studies empirically the inflation rate differentials and their persistence in some currency unions with the aim to draw some conclusions for the working of the ECB monetary policy. KEYWORDS: monetary policy; inflation persistence; currency unions
Keywords: 330; monetary policy; inflation persistence; currency unions